2011
DOI: 10.3171/2010.11.jns101193
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife surgery of meningiomas located in the posterior fossa: factors predictive of outcome and remission

Abstract: Gamma Knife surgery offers an acceptable rate of tumor control for posterior fossa meningiomas and accomplishes this with a low incidence of neurological deficits. In patients selected for GKS, tumor progression is associated with age greater than 65 years and decreasing dose to the tumor margin. Clival- or petrous-based locations are predictive of an increased risk of new or worsening neurological deficit following GKS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 83 publications
3
58
1
3
Order By: Relevance
“…Importantly, the authors in that study reported tumor control rates of 95%, 92%, and 81% at 3, 5, and 10 years after radiosurgery, respectively. 20,22 Similarly, we found that GKRS as the initial treatment for small, mildly symptomatic lesions as well as recurrent or progressive tumors resulted in excellent disease control, and no patient treated initially with GKRS experienced progression over the follow-up period. Low rates of progression/recurrence suggest that longterm disease control for these low-grade lesions is possible with the outlined treatment algorithm, even in the setting of STR, and supports the goal of preserving neurological function whenever possible to maximize patient quality of life.…”
Section: 25mentioning
confidence: 82%
“…Importantly, the authors in that study reported tumor control rates of 95%, 92%, and 81% at 3, 5, and 10 years after radiosurgery, respectively. 20,22 Similarly, we found that GKRS as the initial treatment for small, mildly symptomatic lesions as well as recurrent or progressive tumors resulted in excellent disease control, and no patient treated initially with GKRS experienced progression over the follow-up period. Low rates of progression/recurrence suggest that longterm disease control for these low-grade lesions is possible with the outlined treatment algorithm, even in the setting of STR, and supports the goal of preserving neurological function whenever possible to maximize patient quality of life.…”
Section: 25mentioning
confidence: 82%
“…With a median follow-up of 84 months, tumor control and neurological preservation were achieved in 87% and 91% of patients, respectively. 52 Smaller radiosurgical series confirm the efficacy and safety of radiosurgery for patients with posterior fossa meningiomas, even of the foramen magnum. 53,61 The current series represents the largest one to date for posterior fossa meningiomas treated with radiosurgery (Table 8).…”
Section: Stereotactic Radiosurgerymentioning
confidence: 94%
“…1,16,20,22,27 During the last 20 years, SRS has become an important alternative option for CPA meningiomas. 9,17,26,28 The twin goals of SRS are to maintain or improve function and achieve long-term tumor control.…”
Section: Discussionmentioning
confidence: 99%
“…Nicolato et al 17 documented the reduction of tumor volumes in 55% of patients with posterior fossa meningiomas; they reported that in 40% of patients tumor volume was stable but noted delayed tumor progression in 5%. Starke et al 26 reported that 51% of patients with posterior fossa meningiomas (including 28% of patients with CPA meningiomas) displayed a decrease in tumor volume, 36% had no change in volume, and 13% had an increase in volume. The PFS rates at 3, 5, and 10 years were 98%, 96%, and 78%, respectively.…”
Section: Tumor Control After Srsmentioning
confidence: 99%
See 1 more Smart Citation